Sponge Iron and Its Relation to the Steel Industry - Edward P. Barrett (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
DURING the past few years numerous references have been made in the technical press and Bureau of Mines Bulletin 270 to sponge iron' and so-called "direct metal" processes. The idea has been prevalent that sponge iron and "direct metals" are cheap commodities. In many instances it has been proposed that these processes be used to treat low-grade ores, utilizing low-grade coals as reducing agents. It is questionable whether or not high-grade sponge iron can be made from low-grade materials. Particles contain¬ing iron oxide and gangue become, upon almost complete deoxidation, particles containing metallic' iron and gangue. The possibility of mechanically separating the metallic iron from the gangue in these particles depends . on the physical characteristics of the particular ore under treatment. Some ores, in which the minerals constituting the gangue break free from the iron oxide upon crushing, may be concentrated magnetically after the iron oxides have been reduced to metal. The finely disseminated ores are least amenable to concentration. In general, high-grade sponge iron can only be made from high-grade raw materials. Sponge iron containing small amounts of sulfur can only be made from raw materials containing small amounts of sulfur or by